SOFTWARE METHODS OF ENCODING VIDEO STREAMS USED IN COMPUTER GRAPHICS - Skrupskiy, S. Yu.; Kasyan, K. N. (Radio Electronics, Computer Science, Control, 2024)
There has been performed research on program methods of video streams coding from the view point of the resulting qualitiy, size, parallelism and coding time. Results of experimental research into popular video codecs are presented, the algorithm for choice of a video stream compression method is developed.